Does exercise-induced muscle damage play a role in skeletal muscle hypertrophy? - Schoenfeld, B. J. (The Journal of Strength and Conditioning Research, 2012)
Exercise-induced muscle damage (EIMD) occurs primarily from the performance of unaccustomed exercise, and its severity is modulated by the type, intensity, and duration of training. Although concentric and isometric actions contribute to EIMD, the greatest damage to muscle tissue is seen with eccentric exercise, where muscles are forcibly lengthened. Damage can be specific to just a few macromolecules of tissue or result in large tears in the sarcolemma, basal lamina, and supportive connective tissue, and inducing injury to contractile elements and the cytoskeleton. Although EIMD can have detrimental short-term effects on markers of performance and pain, it has been hypothesized that the associated skeletal muscle inflammation and increased protein turnover are necessary for long-term hypertrophic adaptations. A theoretical basis for this belief has been proposed, whereby the structural changes associated with EIMD influence gene expression, resulting in a strengthening of the tissue and thus protection of the muscle against further injury. Other researchers, however, have questioned this hypothesis, noting that hypertrophy can occur in the relative absence of muscle damage. Therefore, the purpose of this article will be twofold: (a) to extensively review the literature and attempt to determine what, if any, role EIMD plays in promoting skeletal muscle hypertrophy and (b) to make applicable recommendations for resistance training program design.